2021
DOI: 10.3390/su13116138
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Analysis of the Residential Window-to-Wall Ratio Based on Numerical Calculation of Energy Consumption in the Hot-Summer and Cold-Winter Zone of China

Abstract: Along with the rapid urbanization and economic growth of China over the past decades, the thermal comfort needs of the people in this region have risen dramatically, and at the same time, promoting building energy efficiency is cited as part of the major projects in the 14th five-year plan for energy efficiency improvement. In addition, the outbreak of the COVID-19 epidemic has plunged people into long-term panic, and promoted the entire construction industry to think about a healthier and more sustainable liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…According to the results of the questionnaire investigation, existing dwellings with a higher WWR have a higher energy demand and correlate with the simulation results of Yang et al [21]. However, contrary to the findings of Yang et al [21], the simulation results of Liu et al [22] revealed that the heating demand is higher than the cooling demand in China's hot summer and cold winter climates. A WWR of 40 to 50% was proposed as the optimal solution for energy efficiency for the three types of residential buildings, such as a detached house, multi-story building, and high-rise building.…”
Section: Literature Reviewmentioning
confidence: 67%
See 2 more Smart Citations
“…According to the results of the questionnaire investigation, existing dwellings with a higher WWR have a higher energy demand and correlate with the simulation results of Yang et al [21]. However, contrary to the findings of Yang et al [21], the simulation results of Liu et al [22] revealed that the heating demand is higher than the cooling demand in China's hot summer and cold winter climates. A WWR of 40 to 50% was proposed as the optimal solution for energy efficiency for the three types of residential buildings, such as a detached house, multi-story building, and high-rise building.…”
Section: Literature Reviewmentioning
confidence: 67%
“…Liu et al [22] investigated the optimal WWR of residential buildings in the same climates of China. According to the results of the questionnaire investigation, existing dwellings with a higher WWR have a higher energy demand and correlate with the simulation results of Yang et al [21].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the tested students in the experiment were asked to wear similar clothes (a long sleeve, a pair of trousers and a coat) in advance, so it could be predicted that the basic clothing insulation (lcl) was about 0.75 clo [38]. The students were in a quiet sitting position for reading and writing during the experiment, so their metabolic rate (M) could be chosen to be 1.2 met [39]. Finally, the other environmental parameters corresponded to the measured data under different experimental conditions, and the PMV was calculated separately for different experimental conditions.…”
Section: The Experience Surveymentioning
confidence: 99%
“…Once the questionnaires were returned, individual data samples needed to be screened and processed to improve the accuracy and completeness of the underlying data based on the following criteria [76,77].…”
mentioning
confidence: 99%